Elite squash players nutrition knowledge and influencing factors. Issue 1 (10th June 2021) - Turner, Ollie; Mitchell, Nigel; Ruddock, Alan; Purvis, Alison; Ranchordas, Mayur
Abstract: Background: There is a reported mismatch between macronutrient consumption and contemporary macronutrient guidelines in elite standard squash players. Suboptimal dietary practices could be due to a lack of nutrition knowledge among players. Subsequently, the purpose of this study was to assess the sports nutrition knowledge of elite squash players through the Nutrition for Sport Knowledge Questionnaire (NSKQ) and provide an indication of whether players require nutrition support to increase their nutrition knowledge. Methods: This cross-sectional study assessed the nutrition knowledge of 77 elite squash players via the NSKQ over the period of June 2020 to August 2020. Results: Players conveyed average nutrition knowledge with a mean NSKQ score of 48.78 ± 10.06 (56.07% ± 11.56%). There were no significant differences in NSKQ score between male and female players ( p = .532). There was found to be a weak positive association between world ranking and NSKQ score ( r = .208) and age and NSKQ score ( r = .281). Players who had a relevant undergraduate degree (e.g. BSc Sport & Exercise Science) had significantly greater NSKQ score than players with no relevant qualifications ( p = .022). Players who consulted a sports nutritionist to obtain their main source of nutrition information were shown to have significantly greater knowledge than those who acquired knowledge from a sports scientist ( p = .01) or the internet / social media ( p = .007). Conclusions: Players should consult with a sports nutritionist to increase their sport nutrition knowledge. Future research should quantify the effectiveness of a nutritional education intervention at increasing nutrition knowledge in players.